Using qPCR to compare the detection of Plasmodium vivax oocysts and sporozoites in Anopheles farauti mosquitoes between two DNA extraction methods - Timinao, Lincoln; Jamea, Esther W.; Katusele, Michelle; Burkot, Thomas R.; Karl, Stephan (Frontiers in Parasitology, 2023)
Background: Currently, the gold standard to assess parasite developmental stages in mosquitoes is light microscopy. Microscopy can miss low-density infections, is time-consuming and not species-specific. Enzyme-linked immunosorbent assay (ELISA) has been the alternative technique to evaluate the infectivity of mosquitoes especially in field studies however it is semi-quantitative. Molecular techniques that have been used to detect the mosquito stages of malaria parasites including P. vivax. Here, we present a quantitative real-time assay (qPCR) that can be used to detect low-density P. vivax oocyst and sporozoite infections while comparing parasites extracted by the conventional DNA extraction and heating methods. Methods: Colony reared Anopheles farauti mosquitoes were exposed to blood samples collected from infected individuals using a direct membrane feeding assay. The fully fed mosquitoes were kept for 7 and 14 days post-feed before dissection to confirm presence of oocysts and sporozoites. Infected mosquito guts and the salivary glands (with the head and thorax) were stored and DNA was extracted either by heating or by performing conventional column-based DNA extraction. Following DNA extraction the infected samples were subjected to qPCR to detect P. vivax parasites. Results: DNA extraction of 1 or more oocysts by heating resulted in an overall sensitivity of 78% (57/73) and single oocysts infections were detected with a sensitivity of 82% (15/17) in the heating arm. We observed a 60% (18/30) sensitivity with sporozoites where DNA was extracted using the conventional DNA extraction method. We show that the heating method significantly improved the detection of oocysts over conventional DNA extraction. There was no significant difference in the DNA copy numbers when comparing the detection of oocysts from the conventional DNA extraction versus heating. However, we observed that the DNA copy numbers of the sporozoites detected in the heating arm was significantly higher than in the conventional DNA extraction arm. Conclusion: We have adapted a qPCR assay which, when coupled with heating to release DNA reduces sample processing time and cost. Direct qPCR after heating will be a useful tool when investigating transmission blocking vaccines or antimalarials or when evaluating field caught mosquitoes for the presence of malaria parasites.